Evaluation of the Long-Term Strength of Concrete in Building Structures - V. I. Putlyaev; M. N. Berlinova (Железобетонные конструкции)
An approach to estimating the long-term strength of concrete in building structures in the calculation of reinforced concrete structures of buildings and structures of various types is proposed. The process of increasing the initial modulus of concrete deformations in time as a consequence of a certain physicochemical reaction of strength gain is considered. The function of the age of concrete is presented, taking into account the change in the modes of temperature effects during the period of hardening. It is shown that the entropy criterion of strength is more flexible compared to the criterion of the energy barrier of destruction. The application of the entropy strength criterion allows us to take into account the effect of temperature on the long-term strength of concrete.